Accurate crystal structure of ice VI from X-ray diffraction with Hirshfeld atom refinement. (2022) - Chodkiewicz, Michal L.; Gajda, Roman; Lavina, Barbara; Tkachev, Sergey; Prakapenka, Vitali B.; Derac, Przemyslaw; Wozniak, Krzysztof
No abstract available